About the Translation of Poetry - Gusev, Yury (Slavica, 2021)
It is basically impossible to translate poetry into other languages – this follows from the very essence of poetry. But it is impossible not to translate poetry into other languages --this is required by the need to exchange cultural values between different national communities. The translator has to find a compromise between these two mutually exclusive provisions. One of the ways (if not the only one) to achieve this goal is to abandon the requirement of literal accuracy, in order to create an aesthetic effect in a specific cultural and national environment.